2019
DOI: 10.4049/jimmunol.1801565
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 Links Chronic Antigen Stimulation to B Cell Tolerance by Restricting the Survival of Self-Reactive B Cells in the Periphery

Abstract: Nur77 (Nr4a1) belongs to a small family of orphan nuclear receptors that are rapidly induced by BCR stimulation, yet little is known about its function in B cells. We have previously characterized a reporter of Nr4a1 transcription, Nur77-eGFP, in which GFP expression faithfully detects Ag encounter by B cells in vitro and in vivo. In this study, we report that Nur77 expression correlates with the degree of self-reactivity, counterselection, and anergy among individual B cell clones from two distinct BCR transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 80 publications
4
70
0
Order By: Relevance
“…GFP LO B cells 15. In subsequent work, we further excluded the contribution of other immunoreceptor pathways (especially those medi-Tg, and found that dsDNA-reactive λ1 + B cells from these mice turn on GFP reporter expression very early in development, and express much higher levels in maturity than either WT or V H 3H9/κ B cells, consistent with chronic self-antigen stimulation 27. Conversely, V H 3H9 Tg B cells expressing Vλ3 L chains (aka λx) that are known to censor DNA-reactivity express much lower levels of GFP, as do rare "escapee" B cells that express endogenous H chains.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…GFP LO B cells 15. In subsequent work, we further excluded the contribution of other immunoreceptor pathways (especially those medi-Tg, and found that dsDNA-reactive λ1 + B cells from these mice turn on GFP reporter expression very early in development, and express much higher levels in maturity than either WT or V H 3H9/κ B cells, consistent with chronic self-antigen stimulation 27. Conversely, V H 3H9 Tg B cells expressing Vλ3 L chains (aka λx) that are known to censor DNA-reactivity express much lower levels of GFP, as do rare "escapee" B cells that express endogenous H chains.…”
mentioning
confidence: 82%
“…22 This last phenomenon is termed follicular exclusion, depends on the chemokine receptors CXCR5 and CCR7, and has been described not only in the IgHEL model, but also in the V H 3H9 and Ars/A1 models. 27 Indeed, the two-signal model of B cell activation was initially proposed by Bretscher and Cohn in part as a strategy to discriminate self from non-self.…”
Section: The T Wo -S I G Nal Model Of B Cell Ac Tivati On and S Elfmentioning
confidence: 99%
See 3 more Smart Citations